Decision Support System for Employee Performance Evaluation Using SMART Method - Romly, Moh Zaini; Hermanto, Hermanto; Lidimilah, Lukman Fakih (Journal of Artificial Intelligence and Software Engineering, 2025)
In the midst of increasingly fierce industrial competition, objectively assessing employee performance is very important to support accurate managerial decision making. This research develops a web-based Decision Support System (DSS) using the SMART (Simple Multi-Attribute Rating Technique) method to assess employee performance at the CV. Hafas P2S2 Drinking Water Factory. The main innovation of this research is the integration of the SMART method with a web interface specifically designed for small industries, the application of dynamic weights according to management priorities, and the validation of assessment results through the comparison of manual and automatic calculations, which is rarely done in previous studies. The system built with PHP and MySQL through a prototyping approach is proven to be able to assess employee performance objectively, systematically, and efficiently, and reduce subjective bias by 40% compared to manual methods.